Effectiveness of Teaching and Professionalism of Islamic Education Teachers from the Perspective of Educational Psychology - Mahfud, Moh. (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
This study discusses the effectiveness of teaching and the professionalism of Islamic Religious Education teachers from the perspective of educational psychology. Islamic Religious Education, taught at various educational levels, has unique characteristics and content compared to other subjects. Islamic Religious Education teaching emphasizes spiritual and social attitudes, requiring effective teaching approaches. Islamic Religious Education teachers must possess professionalism that includes professional, pedagogical, personal, and social competencies. Teacher professionalism is directly related to their ability to teach effectively, which impacts students' academic achievement. Effective teaching involves a deep understanding of the material, selection of teaching strategies, thorough planning, as well as skills in classroom management, student motivation, and the use of technology. This study uses a literature review method to examine relevant literature on Islamic Religious Education teaching and teacher professionalism, identifying psychological elements that support effective teaching. The results show that professional Islamic Religious Education teachers are those who master various aspects of teaching and the psychological skills needed to create an effective and conducive learning environment.